Factors Affecting The Adoption of Smart Tourism APP Study Among Tourism Stakeholders in Malaysia - Mutia Sobihah, Abd Halim; Mohanad S.S, Abumandil; Ahmad Said Ibrahim, Alshuaibi; Ibrahim Mahmoud, Ibrahim Siam (2020)
Globally, smart tourism market demands has a tremendous impact on the number of tourists visiting Malaysia. Arguably, the tourism sector brings a positive effect to rural communities’ areas through the economic diversification from various business activities. Therefore, the government had put serious attention to this sector as it brings a positive outcome especially to generate more income for local people. However, it has been observed that employees in the tourism industry in Malaysia are lack of awareness in adopting the Islamic smart tourism concept even though they are aware of the diversification of Malaysian' ethnic and culture. For example, lack of knowledge about cultural sensitivity and Halal food will create an issue for foreign tourist and local people. Furthermore, the lack of promotion and information about historical places in Malaysia and interesting places to visit have become the main concern of failing to adopt smart tourism in Malaysia. Therefore, this study intends to examine the impact of Trust (goodwill, predictability, competence), Culture (power distance, uncertainty avoidance, individualism/collectivism, masculinity/femininity), Technology readiness (insecurity, innovativeness, discomfort, complexity), and the moderating role of social media platforms to provide more understanding about the Islamic smart tourism industry in Malaysia.